Trade union and job changes in volatile times: A systematic literature review & future research agenda - Azizan H Morshidi; Kee Y. Sabariah Kee Mohd Yussof; Muhammad Idris Bullare @ Bahari (HRMARS, 2021)
This article attempts to systematically evaluate and synthesise the existing literature in some factors of job changes, how the trade union response to the problem of job changes during uncertain times and outline future research agenda within the domains. This study could demonstrate how the trade union responses to job rearrangement based on diverse combinations of actions and philosophical bearings in these issues from different perspectives. This study also conducted a systematic literature review by relevant criteria from the resource of studies such as Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). It consists of five subsections including search strategy, inclusion and exclusion criteria, eligibility, data abstraction and analysis. Therefore, a systematic search strategy implemented two academic databases, namely Google Scholar and Science Direct. The keywords in the titles and abstracts were used in the search process including "job change", "job re-engineering", "job redesign", "workplace restructuring", "workplace reorganisation", "job reshuffle” and “trade union”. In this study, the results show that there are dimensions of job changes among employees were relevant because the need for improving organisational and some responses trade union towards job changes among employees. The final inclusion was including the selection of sample involving the respond of trade union about job changes during the uncertainties. The present evidence is limited, and numerous research is required on trade union response on changes in job-related domains during uncertain and volatile times.